Investigation on the physical chemical optical and antimicrobial properties of zno and zno ta nanostructures - Aqilah, Kamaruzaman (2021)
To date, nanostructures had received an abundance of attention due to the outstanding intrinsic performances, which mainly depends upon their unique intrinsic properties that have been widely used in revolutionised sectors and industries. Their excellent properties (physical, chemical, optical and biological) are reported to be dependent upon the nanostructure morphology and topology. Hence, producing the nanosize metal oxide, in this case, the ZnO nanostructures, mainly known for its antibacterial properties, is one of the relevant areas of their practical applications. Thus, the work reported the facile synthesis method of a small size range of ZnO nanostructures (mean diameter, dm < 30 nm) in the presence of sodium citrate (SC) using bulk powder ZnO (dm > 5 µm) from hydrothermal method, known for the low cost and environmentally friendly procedure. In this reaction, only SC is used and acts as a surfactant to promote the nanosize ZnO formation. Modifying the surface of the synthesised ZnO nanostructures using the tannic acid (TA) is believed could alter the antibacterial performance of the nanostructures. The function of pH variation (7< pH >3) upon the introduction of TA to the surface of ZnO nanostructure showed the increased of particles aggregation as the pH is lowered due to the increased in the acidic medium. The relationship between the pH change and aggregation of ZnO nanostructures and compared with pure ZnO samples in aqueous solution is discussed in a scope of physical properties, chemical structure, optical property and antimicrobial efficiency. ZnO-TA nanostructures shown to have a slight larger (23nm) and possesses shorter LSPR wavelengths as compared to pure ZnO nanostructures. The calculated Eg of most of the prepared ZnO –TA nanostructures are wider (3.41 eV –3.8 eV) compared to the pure ZnO nanostructures (3.51 eV-3.69 eV). The antimicrobial efficiency of ZnO-TA nanostructures shown to have remarkable performance with the killing percentage of up to 99.69% of S. aureus strain within 24 hours than that of pure ZnO nanostructures (99.39%). Thus, the overall results indicated that TA does influenced the properties of ZnO nanostructures apart from the surface to volume ratio of ZnO nanostructures itself is the important key parameters. The present work could be one of the baseline decision in order to make ZnO nanostructures to our own concept of smart textiles with antibacterial control.